Yowamushi pedal. 8 - Watanabe, Wataru, 1971- (Yowamushi pedaru, 2018)
"Midousuji's goal: hammer Hakone and smash Sohoku! With their members scattered on day two, Sohoku's hopes of winning the inter-high are slipping fast. As Onoda's team fades into the distance, Kyoto-Fushimi and Hakone Academy take center stage. A challenge from Midousuji to Hakone's ace sprinter, Shinkai, soon escalates--transforming their one-on-one battle into a duel between two cycling demons!"--Page [4] of cover.